A brief update on the controversial and opposing roles of Pseudomonas aeruginosa efflux pumps in virulence regulation - Fernandes, Sheryl Erica; Jorth, Peter (Frontiers in Bacteriology, 2023)
Pseudomonas aeruginosa is highly adaptable and constantly mutates to resist natural and synthetic antibiotic stresses. Listed as a serious threat by the Centers for Disease Control, novel antimicrobials are urgently needed for drug resistant P. aeruginosa infections. Multidrug efflux pumps which contribute to antibiotic resistance are genetically encoded, highly conserved, and have evolved long before the rampant clinical use of antibiotics. Hence, efflux pumps may have been selected for functions beyond the mere exclusion of antibiotics. In this review, we discuss recent updates and controversies surrounding how alternative functions of multidrug efflux pumps can influence the virulence of P. aeruginosa. We conclude by highlighting unexpected consequences of targeting efflux pumps with therapies, including potential risks and benefits. Understanding these consequences will be critical to the development of successful therapeutic strategies that consider aspects of both antimicrobial resistance and bacterial pathogenesis.